Math, asked by arunavsen14, 1 month ago

Simplify : 8m –[3m- {2m + 3- 2(4m-4)}] ​

Answers

Answered by khajanchandra111
2

[ 3 m − { 2 m + 3 − 2 ( 4 m − 4 ) } ]

[3m-{2m+3-2(4m-4)}]

= 8 m − [ 3 m − { ( 2 − 8 ) m + ( 3 + 8 } ]

=8m-[3m-{(2-8)m+(3+8}] 8 m − [ 3 m − { − 6 m + 11 m } ] 8m-[3m-{-6m+11m}]

= 8 m − [ 3 m + 6 m − 11 ]

=8m-[3m+6m-11]

= 8 m − [ 9 m − 11 ]

=8m-9m+11=11-m

Answered by akashvijaikishan23
0

Answer:

[3m−{2m+3−2(4m−4)}]

=8m−[3m−{(2−8)m+(3+8}]

8m−[3m−{−6m+11m}]

=8m−[3m+6m−11]

=8m−[9m−11]

=8m-9m+11=11-m

Similar questions